Nilai-Nilai Didaktis Dalam Buku Cerita Rakyat Pangeran Sutan Galumat - Fitri, Jesica Indah; Kamaruddin, Kamaruddin; Nurfadilah, Nurfadilah (Universitas Batanghari Jambi, 2023)
This study aims to describe the didactic values in the folklore book Prince Sutan Galumat. The formulation of the problem in this research is what didactic values are contained in the folklore book of Prince Sutan Galumat. This study uses qualitative methods and descriptive research types. The data source for this research is the folklore book of Prince Sutan Galumat. The data in this study were obtained from descriptions, sentences, dialogue quotes. Collecting data in research using library techniques. The results of this study are (1) moral values, namely values related to character, values related to morals (2) intelligence values, namely values related to logical thinking, values related to creative thinking, (3 ) social values, namely, values related to a sense of responsibility, values related to a sense of tolerance (4) religious values, namely, values related to spirituality, values related to being virtuous, values related to being in the way of God (5) the value of independence, namely, the value related to the ability to make decisions, the value related to self-confidence, the value related to responsibility for what is done (6) the value of patience, namely, the value related to not giving up easily, the value related to always forgive, a value related to not having a grudge. Prince Sutan Galumat's folklore book can be used as a medium to instill didactic values in students. The folklore book of Prince Sutan Galumat can be used as an alternative teaching material in learning Indonesian. Prince Sutan Galumat's folklore book can be used as a medium to instill didactic values in students. The results of the research can be used as a reference source for other researchers who want to research in the same research with different studies and can be used as guidelines or principles in living life.